Cancun update : negotiations on WTO rules (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Notes the prospects for Cancun. Provides a background to the topic and lists mandated deadlines. Focuses on the current state of play, highlighting issues such as: anti-dumping; subsidies and countervailing measures; special and differential treatment; non-accountable subsidies amd regional trade agreements.
Keywords: TRADE NEGOTIATIONS